Discourses of Collective Spirituality and Turkish Islamic Ethics: An Inquiry into Transcendence, Connectedness, and Virtuousness in Anatolian Tigers - Karakas, Fahri (Journal of business ethics, 2015)
Based on case studies and qualitative interviews conducted with 40 stakeholders in five SMEs, or so called Anatolian tigers, in Turkey, this article has explored what collective spirituality and Turkish Islamic business ethics entail and how they shape organizational values using diverse stakeholder perspectives. The study has revealed six emergent discourses around collective spirituality and Islamic business ethics: Flying with both wings; striving to transcend egos; being devoted to each other; treating people as whole persons; upholding an ethics of compassion; and leaving a legacy for future generations. These discourses are organized around three themes of collective spirituality, respectively: Transcendence, connectedness, and virtuousness.